Animal Minds and Neuroimaging: Bridging the Gap between Science and Ethics? - Buller, Tom (Cambridge quarterly of healthcare ethics, 2014)
As Colin Allen has argued, discussions between science and ethics about the mentality and moral status of nonhuman animals often stall on account of the fact that the properties that ethics presents as evidence of animal mentality and moral status, namely consciousness and sentience, are not observable “scientifically respectable” properties. In order to further discussion between science and ethics, it seems, therefore, that we need to identify properties that would satisfy both domains.In this article I examine the mentality and moral status of nonhuman animals from the perspective of neuroethics. By adopting this perspective, we can see how advances in neuroimaging regarding (1) research into the neurobiology of pain, (2) “brain reading,” and (3) the minimally conscious state may enable us to identify properties that help bridge the gap between science and ethics, and hence help further the debate about the mentality and moral status of nonhuman animals.